Seeing is Believing : Poverty in the Palestinian Territories - Vishwanath, Tara; Blankespoor, Brian; Calandra, Faythe; Krishnan, Nandini; Mahadevan, Meera; Yoshida, Nobuo (World Bank, Washington, DC, 2015)
The Palestinian Territories have a uniquely fragmented geography, characterized by the isolation of Gaza from the rest of the world, and the man-made barriers to mobility within the West Bank. The internal mobility restrictions imposed by Israel, unique to the West Bank, play an important role in explaining spatial variations in outcomes within the West Bank. This is strikingly analogous to the role of Gaza s external barriers in explaining the divergence between the West Bank and Gaza. These have consequences for poverty and economic development. Detailed analysis using a series of labor force and household surveys were undertaken as part of the West Bank and Gaza Poverty and Inclusion Assessment, Coping with Conflict? The analysis shows that over the last decade, internal and external barriers have been associated with tremendous constraints to growth and investment, which is evident in high rates of unemployment, especially in Gaza and among women and youth.